2005
DOI: 10.1057/palgrave.jibs.8400160
|View full text |Cite
|
Sign up to set email alerts
|

The impact of political risk on the volatility of stock returns: the case of Canada

Abstract: This paper examines the impact of political risk in Canada on the volatility of stock returns. Our results suggest that political news associated with the possible separation of Quebec from Canada plays an important role in the volatility of stock returns. However, our evidence indicates that investors do not require a risk premium, supporting the idea that political risk is diversifiable. We also show that stock return volatility varies with the degree of a firm's exposure to political risk, namely, the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 56 publications
5
43
2
1
Order By: Relevance
“… At this stage, we would like to make a distinction between the contribution of this study and that of the previous literature on political risk. While it is often argued that political risk should be diversifiable in the long run from an investor's standpoint, (see, among others, Butler and Joaquim 1998) and that the empirical evidence is consistent with this view (Beaulieu, Cosset, and Essaddam 2005), this study clearly finds, for a very important political event in Canada for which the outcome could not be anticipated, that political uncertainty impacted on stock returns on a relatively short time span. The fact that Brown, Harlow, and Ticnic (1988) find that the effect of uncertainty resolution is only transitory in their simulations might explain why we find an effect in this event study but none when the long‐run effect of political risk is considered. …”
mentioning
confidence: 47%
See 1 more Smart Citation
“… At this stage, we would like to make a distinction between the contribution of this study and that of the previous literature on political risk. While it is often argued that political risk should be diversifiable in the long run from an investor's standpoint, (see, among others, Butler and Joaquim 1998) and that the empirical evidence is consistent with this view (Beaulieu, Cosset, and Essaddam 2005), this study clearly finds, for a very important political event in Canada for which the outcome could not be anticipated, that political uncertainty impacted on stock returns on a relatively short time span. The fact that Brown, Harlow, and Ticnic (1988) find that the effect of uncertainty resolution is only transitory in their simulations might explain why we find an effect in this event study but none when the long‐run effect of political risk is considered. …”
mentioning
confidence: 47%
“…International foreign investment could create new risk factors such as political risk and foreign exchange risk. However, several studies maintain that these new risks are diversifiable (e.g., Beaulieu, Cosset, and Essaddam 2005; Goldberg and Heflin 1995). Multinational companies operate in a number of domestic markets from which they can minimize the impact of fluctuations in interest rates, cost of input, and salaries by transferring their operations from one market to another.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…But most recently, Hudson, Keasey and Dempsey (1998) found that, while short‐term price movements reacted to opinion polls in the run‐up to and including elections, there was no statistically significant evidence of a difference in nominal or real returns between Tory and Labour governments. In general, most recent research in the United States, including Bohl, Dopke and Pierdzioch (2008) and Ferri (2008), and elsewhere, such as Beaulieu, Cosset and Essaddam (2005, 2006), Li and Born (2006) and Lim, Brooks and Hinich (2008), confirm that elections and other political events have short‐term impacts on markets.…”
Section: Previous Findingsmentioning
confidence: 86%
“…Furthermore, we posit that large multinational companies in the natural resource sector may be more capable of undertaking investments in risky locations due to the extent of their diversification. In a similar context, Beaulieu, Cosset, and Essaddam (2005) contend that a multinational firm which is headquartered in Quebec but has operations in other countries can diversify away political risk and would be less affected by a possible Quebec independence than a company conducting business solely at local level. In contrast, small companies often have a large proportion of their assets and revenue streams concentrated in a single country, which heightens their vulnerability to specific country risk.…”
Section: Discussion Of Analysismentioning
confidence: 99%